Targeted DNA sequencing of high-grade serous ovarian carcinoma reveals association of TP53 mutations with platinum resistance when combined with gene expression - Holý, Petr; Hlaváč, Viktor; Šeborová, Karolína; Šůsová, Simona; Tesařová, Tereza; Rob, Lukáš; Hruda, Martin; Bouda, Jiří; Bartáková, Alena; Mrhalová, Marcela; Kopečková, Kateřina; Al Obeed Allah, Mohammad; et al. (International journal of cancer, 2024)
High-grade serous ovarian carcinoma (HGSC) is the most common subtype of ovarian cancer and is among the most fatal gynecological malignancies worldwide, due to late diagnosis at advanced stages and frequent therapy resistance. In 47 HGSC patients, we assessed somatic and germline genetic variability of a custom panel of 144 known or suspected HGSC-related genes by high-coverage targeted DNA sequencing to identify the genetic determinants associated with resistance to platinum-based therapy. In the germline, the most mutated genes were DNAH14 (17%), RAD51B (17%), CFTR (13%), BRCA1 (11%), and RAD51 (11%). Somatically, the most mutated gene was TP53 (98%), followed by CSMD1/2/3 (19/19/36%), and CFTR (23%). Results were compared with those from whole exome sequencing of a similar set of 35 HGSC patients. Somatic variants in TP53 were also validated using GENIE data of 1287 HGSC samples. Our approach showed increased prevalence of high impact somatic and germline mutations, especially those affecting splice sites of TP53, compared to validation datasets. Furthermore, nonsense TP53 somatic mutations were negatively associated with patient survival. Elevated TP53 transcript levels were associated with platinum resistance and presence of TP53 missense mutations, while decreased TP53 levels were found in tumors carrying mutations with predicted high impact, which was confirmed in The Cancer Genome Atlas data (n = 260). Targeted DNA sequencing of TP53 combined with transcript quantification may contribute to the concept of precision oncology of HGSC. Future studies should explore targeting the p53 pathway based on specific mutation types and co-analyze the expression and mutational profiles of other key cancer genes.
Keywords: Gene Expression Regulation, Neoplastic; zárodečné mutace; mutace; Ovarian Neoplasms; sekvenování exomu; regulace genové exprese u nádorů; platina; chemorezistence; Adult; Platinum; Aged; dospělí; senioři; nádorový supresorový protein p53; nádory vaječníků; Cystadenocarcinoma, Serous; Germ-Line Mutation; serózní cystadenokarcinom; lidé; ženské pohlaví; Humans; Drug Resistance, Neoplasm; Mutation; Female; Exome Sequencing; lidé středního věku; Tumor Suppressor Protein p53; Middle Aged